2015
DOI: 10.1148/radiol.15141251
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic Value of Cervical Nodal Necrosis in Nasopharyngeal Carcinoma: Analysis of 1800 Patients with Positive Cervical Nodal Metastasis at MR Imaging

Abstract: Purpose:To evaluate the prognostic value of cervical nodal necrosis (CNN) in patients with nasopharyngeal carcinoma (NPC) with magnetic resonance (MR) imaging. Materials and Methods:This was an institutional review board-approved retrospective study of 1800 patients with newly diagnosed stage T1, 4N1, 3M0 NPC who were treated with definitive radiation therapy, with or without chemotherapy, between January 2007 and December 2009; the requirement to obtain informed consent was waived. MR images were reviewed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 18 publications
12
71
0
Order By: Relevance
“…In a study of 786 patients with npc and positive cervical lymph nodes, Mao et al 9 reported that the incidence of lymph node necrosis was only 26.5%. In our study, the incidence of lymph node necrosis was much higher (43.3%, 91 of 210 patients) and similar to the incidence described by Lan et al 11 . In the study by Mao et al 9 , lymph node necrosis did not have a significant association with survival in npc patients; however, that result might reflect the analysis of a relatively small cohort.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In a study of 786 patients with npc and positive cervical lymph nodes, Mao et al 9 reported that the incidence of lymph node necrosis was only 26.5%. In our study, the incidence of lymph node necrosis was much higher (43.3%, 91 of 210 patients) and similar to the incidence described by Lan et al 11 . In the study by Mao et al 9 , lymph node necrosis did not have a significant association with survival in npc patients; however, that result might reflect the analysis of a relatively small cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Those results indicate that the retropharyngeal lymph nodes and the cervical level ii nodes might both be the first-echelon nodes in npc, perhaps partly because the lymphatic vessels of the nasopharynx drain in two general directions, lateral and medial 5,13 . The primary drainage is the lateral pathway, which drains the lateral nasopharynx and flows into the lateral half of the upper internal jugular chain or into the lateral retropharyngeal lymph node 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore used both contrast-enhanced CT and MRI to improve both accuracy and sensitivity of imaging results, following recommendations set forth by King et al,17 wherein a cervical node was diagnosed as necrotic if there was a focal area of low attenuation with or without a surrounding rim of enhancement on CT imaging and if there was a focal area of high signal intensity on T2-weighted images or a focal area of low signal intensity on T1-weighted images (with or without a surrounding rim of enhancement on MRI). While the incidence of CNN in our study population was 45% (85 of 189 patients), other studies have reported CNN ranges from 20% to 44% in NPC patients 17,23,24,29. Importantly, our study excluded early-stage patients, who were included in other studies; 45% reported herein is therefore reasonable.…”
Section: Discussionmentioning
confidence: 60%
“…Multivariate analysis identified CNN as an independent, negative prognostic factor for PFS and OS. Recently, a study by Lan et al24 evaluated the prognostic value of CNN and determined that CNN negatively affected OS, DFS, RRFS, and DMFS in NPC patients. A study by Tang et al26 also demonstrated that necrotic RLN metastases have a negative effect on treatment failure, distant failure, and locoregional recurrence in NPC patients.…”
Section: Discussionmentioning
confidence: 99%